Cost accounting : - Horngren, Charles T. (Prentice-Hall, 1972)
Cost Accounting defined the cost accounting market and continues to innovate today by consistently integrating the most current practice and theory into the text. This acclaimed, market-leading text emphasizes the basic theme of “different costs for different purposes,” and reaches beyond cost accounting procedures to consider concepts, analyses, and management.